Allelic spectrum of formiminotransferase‐cyclodeaminase gene variants in individuals with formiminoglutamic aciduria - Majumdar, Ramanath (Mol Genet Genomic Med, 2017)
BACKGROUND: Elevated plasma and urine formiminoglutamic acid (FIGLU) levels are commonly indicative of formiminoglutamic aciduria (OMIM #229100), a poorly understood autosomal recessive disorder of histidine and folate metabolism, resulting from formiminotransferase‐cyclodeaminase (FTCD) deficiency, a bifunctional enzyme encoded by FTCD. METHODS: In order to further understanding about the molecular alterations that contribute to FIGLU‐uria, we sequenced FTCD in 20 individuals with putative FTCD deficiency and varying laboratory findings, including increased FIGLU excretion. RESULTS: Individuals tested had biallelic loss‐of‐function variants in protein‐coding regions of FTCD. The FTCD allelic spectrum comprised of 12 distinct variants including 5 missense alterations that replace conserved amino acid residues (c.223A>C, c.266A>G, c.319T>C, c.430G>A, c.514G>T), an in‐frame deletion (c.1373_1375delTGG), with the remaining alterations predicted to affect mRNA processing/stability. These included two frameshift variants (c.990dup, c.1366dup) and four nonsense variants (c.337C>T, c.451A>T, c.763C>T, c.1607T>A). CONCLUSION: We observed additional FTCD alleles leading to urinary FIGLU elevations, and thus, providing molecular evidence of FTCD deficiency in cases identified by newborn screening or clinical biochemical genetic laboratory testing.